A CORRELATION BETWEEN SKIMMING SKILL AND READING COMPREHENSION ACHIVEMENT OF THE STUDENTS OF HIGH SCHOOL IN BEKASI - sarsono sarsono (Journal of English Language and Literature (JELL), 2017)
The research is aimed at proving or determining correlation between skimming skill and reading comprehension achivement of the students of high school. The collection of data was carried out by questionnaire, the data was analyzed statistically by Person Product Moment Correlation of coefficient correlation preceded by Lillifors normality test as prerequisite analysis ( Lo < L-table ). The research found that ; 1) Based on Person Product Moment Correlation, reveals r = 0,969, while the r-table for degree of freedom(df) = (N-2) = 40 and the significance level 5% (0,05) is 0,304. Therefore the Null Hypothesis (Ho) which expresses that there is no significant Correlation Between Skimming Skill and Reading Comprehension achievement is rejected, and the alternative Hypothesis (Ha), which expresses that there is significant Correlation Between Skimming Skill and Reading Comprehension Achievement can be accepted. 1) There is a significant correlation with t-test (t-count) is 98,80 and degree of freedom (df) n-2 = 40, at level 5 % (0,05) sig ( two tail test), t-table is 2,326 t-count > t –table ( 98,80 > 2,326, so Ho is rejected and Ha is accepted. It means that the correlation has positive correlation. 2) The degree of correlation based on the table of coefficient correlation (r) is 0.969. the interval coefficient relation is between 0,80 and 1,00, so the correlation is very strong.